An overview of consumer complaining behavior and the choice of complaint channels in service industry - Patwary, Ataul Karim (Universiti Malaysia Perlis, 2016)
In extensive view of consumers’ complaint behavior research area, choosing specific complaint channels has been considered as a phenomenon. Although, existing literatures explored much on the consumption behavior of products and services, exploring on the choice of complaint channels still in infancy level.Moreover, investigation of channel-choice for complaining is not done extensively.This study provides a brief overview on complaint responses and classifications of consumer complaining behavior (CCB).Consequently, a suitable classification of complaint reactions with regard to complaint channels is discussed in details.The researchers suggested three aspects which are vital for service providers in order to retain existing consumers and seek for new consumers and acquire positive word of mouth; (1) the service providers required to encourage consumers to make complains (2) complaint channels should be easily accessible for consumers and (3) existence of smooth complaint handling process. The development of this extensive literature review, suggestions and conceptualization would be helpful for researchers while they aim for further empirical investigation of consumers complaining behavior and complaint channels.